2016
DOI: 10.1126/science.aac5560
|View full text |Cite
|
Sign up to set email alerts
|

Dietary antigens limit mucosal immunity by inducing regulatory T cells in the small intestine

Abstract: Dietary antigens are normally rendered nonimmunogenic through a poorly understood "oral tolerance" mechanism that involves immunosuppressive regulatory T (Treg) cells, especially Treg cells induced from conventional T cells in the periphery (pTreg cells). Although orally introducing nominal protein antigens is known to induce such pTreg cells, whether a typical diet induces a population of pTreg cells under normal conditions thus far has been unknown. By using germ-free mice raised and bred on an elemental die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
434
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(453 citation statements)
references
References 33 publications
(43 reference statements)
17
434
0
2
Order By: Relevance
“…However, the complete antigen sequestration paradigm itself has neither been found to develop a prolonged period of MGCA-specific tolerance due to the emergence of MGCA-specific Tregs (36). Thus, postvasectomy autoimmunity occurred only when it was accompanied by partial Treg depletion with an anti-CD25 mAb (32,36), a finding more likened to the concomitant effector T cell and Treg responses to foreign antigens described in food allergy (37) and in viral infections (38). Therefore, postvasectomy responses resemble the responses to immunogenic "foreign" antigens; moreover, the Ab repertoire is narrower than expected and suggests the existence of tolerance to other MGCA (36).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, the complete antigen sequestration paradigm itself has neither been found to develop a prolonged period of MGCA-specific tolerance due to the emergence of MGCA-specific Tregs (36). Thus, postvasectomy autoimmunity occurred only when it was accompanied by partial Treg depletion with an anti-CD25 mAb (32,36), a finding more likened to the concomitant effector T cell and Treg responses to foreign antigens described in food allergy (37) and in viral infections (38). Therefore, postvasectomy responses resemble the responses to immunogenic "foreign" antigens; moreover, the Ab repertoire is narrower than expected and suggests the existence of tolerance to other MGCA (36).…”
Section: Introductionmentioning
confidence: 92%
“…Because the EAO resistance state was reversed by neutralization with an anti-PD-L1 Ab, but not an anti-PD-1 Ab (36), and because PD-L1, but not PD-1, is required for peripheral Treg induction (62,63), we surmised that the post-Vx EAO resistance state was partially attributed to peripheral Treg induction against the exposed MGCA. Therefore, in addition to maintaining physiological tolerance to NS-MGCA, Tregs can be induced by the "foreign" S-MGCA in a manner similar to the Treg response to foreign antigens (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…53,54 Moreover, recent evidence from studies in mice suggests that the development of oral tolerance to food antigens may be regulated by the influence of both microbiome-induced and dietary antigen-induced populations of peripheral Tregs which develop outside of the thymus from conventional T cells. 55 And recent studies in a general population-derived birth cohort provided evidence that infants at risk to develop food allergy can display a hyper-responsive innate immune response at birth, which, together with mucosally-derived TGF-β, might both promote nonclassic differention of Th2 lymphocytes and impair the function of natural Treg cells. 56 It will be of interest to confirm these interesting findings in other populations, as well as to investigate how such processes might be influenced by various effects of microbiomes and/or the timing of introduction of food allergens.…”
Section: Prevention Preventing the Development Of Diseasementioning
confidence: 99%
“…Emerging evidence has shown that the periphery immune system is Oral, nasal, and skin-patch vaccines have been developed to elicit protective immunity by noninvasive delivery of vaccines to the mucocutaneous interface. Although oral vaccines against polio and cholera have been deployed with varying degrees of success [18], progress to develop oral vaccines is limited owing to multiple obstacles including interference from food particles and gut microbiome, enzymatic digestion of antigens, inefficient antigen delivery across epithelial cells into mucosa-associated lymphoid tissue (MALT) in the gastrointestinal (GI) tract, enteropathy found in developing countries [36,37], as well as the oral mucosal immune system which tends to induce tolerance upon exposure to dietary antigens that trigger the generation of retinoid-related orphan receptor gamma t (RORγt)-deficient regulatory T cells in the GI tract [38]. The demonstration that oral vaccines' efficacy could be improved by targeting intestinal microfold (M) cells with biodegradable microparticles [39] or feeding vaccinees with a buffer solution in advance [40] offers hope for enhancing the potency of oral vaccines.…”
Section: Noninvasive Vaccination As a Juggernaut To Minimize Vaccinatmentioning
confidence: 99%